Pemeriksaan Ektoparasit pada Berbagai Komoditas Budidaya Perikanan Payau - Yunarty Yunarty; Ardana Kurniaji; Kasmatang Kasmatang (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Ectoparasites is a type of parasite that is generally found infecting the external organs of their host's body. Knowledge of the types of parasites and the host are reviewed as an effort to control parasitic attacks. This study aimed to examine the types of ectoparasites in various brackish aquaculture commodities. Research procedurewereincluding preparation of tools and materials, sampling, observation of clinical symptoms, necropsy, observation of parasites and data processing. This study used purposive sampling with 28 samples obtained from several locations consisting of 5 nemo fish (A. ocellaris), 2 tilapia (O. niloticus), 1 snapper (L. calcarifer), 3 crab (P. pelagicus), 5 mangrove crabs (Scylla spp.), 12 vaname shrimp (L. vannamei). The data obtained were analyzed descriptively by comparison between the commodities and the types of parasites found. The results showed that the clinical symptoms of each commodity were different, namely loss of appetite, inactivity, slow growth and morphological changes.Crab and mangrove crab were not showing clinical symptoms. Parasitic infections were found in all types of commodities except snapper fry, crab larvae, broodstock and vannamei fry. The types of parasites found were Cryptocaryon sp., Tricodina sp., Gyrodactilus sp., Ascarophis sp., Dactylogyrus sp., Octolasmis sp., Rabdostyla sp., Zoothamnium sp., Vorticella sp., Acinata sp. Each type of parasite has different characteristics, properties and control.